Bassini inguinal hernia repair: Obsolete or still a viable surgical option? A single center cohort study. (October 2021) - Tse, Wayne; Johns, William; Maher, James; Rivers, Jeannie; Miller, Thomas
Abstract: Background: Most inguinal hernias are presently repaired using some type of mesh technique. This mesh can be placed through an inguinal incision or positioned through a laparoscopic approach. Either way, results have been impressive including a low recurrence rate, minimal pain and a rapid return to work and normal activity compared to tissue based approaches. Notwithstanding these results, there is still a subset of patients who, for various reasons, are strongly opposed to having a mesh repair. This study summarizes our 13 year experience with such patients and why the Bassini hernia repair is a viable surgical option in these individuals. Methods: Patients undergoing a Bassini repair at our institution from 2006 to 2014 were analyzed for long-term durability of the repair, complications and recurrence rate. Results: Of 203 patients studied (average age 65; 99% male), 205 repairs (two patients had bilateral repairs) were evaluated. Seven documented recurrences (3.7%) were identified. Post-operative complications were relatively minor and easily managed. They included 22 patients (10.8%) with a wound hematoma/seroma, 17 (8.4%) with urinary retention, and four (2%) with testicular ischemia not requiring orchiectomy. Pain problems (10.3%) were generally transient and resolved in a period of weeks. In those patients who did not die from co-morbid disease, long term durability of repair (≥5 years) was quite common. Conclusion: Low recurrence rate, long term durability and relatively minor complications indicate that the Bassini repair is still a good surgical option in patients opposed to a mesh repair. As such, we argue that it is not obsolete but still remains a viable surgical option in selected patients. Highlights: Mesh repair is not suitable for all patients with inguinal hernias. Tissue repair should still be part of the surgeon's armamentation in dealing with inguinal hernias. The Bassini inguinal repair can be performed with an acceptable recurrence rate and long term durability.